Conformally coated BiVO4 nanodots on porosity-controlled WO3 nanorods as highly efficient type II heterojunction photoanodes for water oxidation. (October 2016) - Lee, Mi Gyoung; Kim, Do Hong; Sohn, Woonbae; Moon, Cheon Woo; Park, Hoonkee; Lee, Sanghan; Jang, Ho Won
Abstract: Bismuth vanadate (BiVO4 ) has become a hot topic for solar hydrogen generation by water oxidation due to its appropriate band edges, and narrow band gap. However, the actual conversion efficiency achieved with BiVO4 -based photoanodes is considerably less than the theoretical values because of drawbacks such as poor electron transportation and slow kinetics of oxygen evolution. In these respects, formation of nanostructured heterojunctions is considered to have a marked effect in terms of improving the photoactivities of BiVO4 photoanodes since it is possible to enhance the charge transfer at the interface and increase light absorption significantly. Herein, we report the synthesis and photoelectrochemical (PEC) properties of various BiVO4 -based heterojunction anodes based on stoichiometric BiVO4 by pulsed electrodeposition. We show that WO3 is the optimum bottom layer for a type II band system with BiVO4 among various metal oxides. It is revealed that the photocurrent density of bare WO3 nanorods can be changed drastically by controlling the porosity and aspect ratio and thus BiVO4 /WO3 heterojunction anodes show as similar tendency to bare WO3 nanorods. Under the optimum conditions, a BiVO4 /WO3 heterojunction anode can lead to a high photocurrent density of 4.55 mA/cm 2 and an incident photon to current conversion efficiency of 80% at 1.23 V versus a reversible hydrogen electrode without additional catalyst. Cross-sectional transmission electron microscopy shows that dot-like BiVO4 is well decorated on the entire surface of WO3 nanorods. This systematic study provides a viewpoint on the crucial role of the active area of the bottom layer for high-performance BiVO4 -based type II heterojunction photoanodes, and the proposed concept is applicable to various photoelectrode systems. Graphical abstract: Highlights: This is the first systematic study between PEC properties and band structures of BiVO4 -based heterojunction. Control of active areas of WO3 is the key to achieve high PEC efficiency of BiVO4 /WO3. Conformally coated 3D BiVO4 nanodots on the surface of WO3 -NRs was firstly reported. Our BiVO4 /WO3 show the highest photocurrent without catalyst or doping reported to date.